Identifikasi Habitat Burung Maleo (Macrocephalon maleo) Menggunakan Sistem Informasi Geografi Di Cagar Alam Panua Provinsi Gorontalo - Nurma Rosalia; Marini Susanti Hamidun; Iswan Dunggio (Konservasi Hayati, 2024)
Maleo (Macrocephalon maleo) is an endemic bird species found in various regions of Sulawesi Island, including the Panua Nature Reserve in Pohuwato Regency, Gorontalo Province. The Maleo population is suspected to be declining due to habitat destruction. Urgent action is required to address this issue, including the mapping of suitable Maleo habitats. The objective of this research is to identify Maleo habitats based on landscape analysis using Geographic Information System (GIS) technology. Parameters used to assess habitat suitability include geothermal resources, land cover, soil type, accessibility, and slope. The data analysis employs GIS tools, utilizing a weighting and scoring system across several landscape variables such as land cover, soil type, geothermal resources, accessibility, and slope. The findings reveal the presence of geothermal resources within Panua Nature Reserve. The soil types predominantly consist of ultisols or yellow-red podzolic soils, with the fluvial district suborder being particularly preferred as Maleo habitat, scattered along riverbanks and coastal areas. The land cover is dominated by secondary and primary forests, serving as crucial food and shelter sources for Maleos. Slope conditions in Panua Nature Reserve are primarily steep, resulting in challenging accessibility across much of the area. Difficult access is particularly prevalent in the northern region, whereas easier access is found along the coastal areas, which serve as nesting habitats for Maleos. Based on the analysis using GIS-assisted scoring, the suitable Maleo habitat area in Panua Nature Reserve measures approximately 26,588.36 hectares, while the unsuitable area spans 550.49 hectares